Efficacy and Tolerability of Second-Generation Antipsychotics in Children and Adolescents With Schizophrenia - Kumra, Sanjiv (Oxford University Press, 2008)
Early-onset schizophrenia-spectrum (EOSS) disorders (onset of psychotic symptoms before 18 years of age) represent a severe variant associated with significant chronic functional impairment and poor response to antipsychotic treatment. All drugs with proven antipsychotic effects block dopamine D(2) receptors to some degree. The ongoing development of the dopamine and other neurotransmitter receptor systems during childhood and adolescence may affect clinical response and susceptibility to side effects in youth. A literature search was conducted of clinical trials of antipsychotics in children and adolescents with EOSS disorders between 1980 and 2007 from the Medline database, reference lists, and conference proceedings. Trials were limited to double-blind studies of duration of 4 or more weeks that included 15 or more patients. Ten clinical trials were identified. Antipsychotic medications were consistently found to reduce the severity of psychotic symptoms in children and adolescents when compared with placebo. The superiority of clozapine has been now demonstrated relative to haloperidol, standard-dose olanzapine, and “high-dose” olanzapine for EOSS disorders. However, limited comparative data are available regarding whether there are differences among the remaining second-generation antipsychotics (SGAs) in clinical effectiveness. The available data from short-term studies suggest that youth might be more sensitive than adults to developing antipsychotic-related adverse side effects (eg, extrapyramidal side effects, sedation, prolactin elevation, weight gain). In addition, preliminary data suggest that SGA use can lead to the development of diabetes in some youth, a disease which itself carries with it significant morbidity and mortality. Such a substantial risk points to the urgent need to develop therapeutic strategies to prevent and/or mitigate weight gain and diabetes early in the course of treatment in this population.